Comparison of Analytical Methods for the Validation of the Sterility of Autologous Serum Eye Drops - Blaser, Frank; Meneau, Isabelle; Schneider, Jana; Wiedler, Jürg; Hinrikson, Hanspeter; Barthelmes, Daniel; Zweifel, Sandrine; Bajka, Anahita; Said, Sadiq; Wiest, Maximilian Robert Justus (Klinische Monatsblätter für Augenheilkunde, 2025)
Purpose For specific samples, there are different methods and requirements for testing sterility. Blood and blood products are analyzed using automated blood culture methods, while pharmacopeial sterility is assessed using membrane filtration or direct inoculation according to the European Pharmacopoeia (Ph. Eur. 2.6.1.) to detect microbial growth. As autologous serum eye drops (ASEDs) may be viewed as both a blood product and a classical drug, the Swiss legislator has classified these as non-standardizable drugs, and thus, the pharmacopeial requirements apply. This study investigates ASED preparations with respect to the performance of a common automated blood culture system, BD BACTEC, in detecting aerobic and anaerobic bacteria and fungi in ASED preparations, with pharmacopeial sterility testing using agar plate cultures.Methods Based on the European Pharmacopoeia, we inoculated sterile filtered blood serum with BioBalls of the six reference strains at a low concentration of three colony-forming units per milliliter (CFU/mL). A test battery of three different BD BACTEC culture media (hereafter referred to as Trio-BACTEC : BD BACTEC Plus Aerobic/F-Medium, BD BACTEC Lytic/10 Anaerobic/F-Medium, BD BACTEC Mycosis IC/F-Medium) and three agar plates [Tryptic Soy Agar (TSA), Chocolate Blood Agar, Sabouraudʼs Dextrose Agar] were inoculated per strain. We incubated the Trio- BACTEC in the BD BACTEC Blood Culture System at 35 °C for 5 days, the TSA and Chocolate plates at 35 °C for 5 days, and the Sabouraud plates at 25 °C for 7 days. We confirmed positive growth signals by microscopy or MALDI-ToF mass spectrometry and included negative controls.Results We detected all reference strains using BACTEC and agar plates. No growth was observed in the negative controls. Overall, growth detection by BACTEC and agar plates was comparable, except for Aspergillus brasiliensis and Candida albicans, which was detected after 1 day on solid media and after 2 days on BACTEC.Conclusion This study demonstrates the comparability of sensitivity and detection speed using the automated blood culture method and agar plates for sterility validation of ASED, even at low bacterial and fungal contamination levels.
Keywords: cornea; autologous serum eye drops; sterility